The Paradoxical World of Psycho-Pass Anime Series - Natasha Harly; Liem Satya Limanta (Institute of Research and Community Outreach - Petra Christian University, 2021)
Psycho-Pass is one of the most well-known examples of dystopian anime. The story is set in 22nd century Japan, where the country is ruled by the Sibyl System. The world is portrayed to be an ideal world that is seemingly crime-free, yet the world also contained many problems that offset how ideal it seemed. In this paper, we are concerned about how Psycho-Pass can be categorized as a paradoxical world. Therefore, we aim to show the ways that the world of Psycho-Pass is indeed paradoxical by using utopia and dystopia theories. Through our analysis, we found that elements of both utopia and dystopia are present in Psycho-Pass. The world of Psycho-Pass is paradoxical in that it is ideal and faulty at the same time. Keywords: anime, paradoxical, utopia, dystopia.